Performance Evaluation Of An SCM/WDM Fiber Microcellular Mobile Communication System Based On IM/DD - Subramaniam, Shamini (2005)
The performance of an SCM-WDM micro-cellular mobile communication system based on IM/DD is evaluated using simulation. The aim is to evaluate the Carrier to Noise Ratio (CNR) at the receiver taking into account transmission impairments due to non linear effects namely Cross Phase Modulation (XPM).